Traditional Accounting Practices in The Financial Management of The Jaranan Rogo Jati Putro Community in Sidowarek Ngoro Village - Yola Nindy Aprillia; Nur Anisah (Asosiasi Pengelola Publikasi Ilmiah (APPI) PT PGRI, 2025)
This study aims to describe traditional accounting practices in the financial management of the Rogo Jati Putro Horse Dance Community in Sidowarek Village and analyze its role in the accountability and sustainability of the arts community. The study uses a qualitative approach with a case study method through interviews, participatory observation, and documentation of the chairperson, members, and cultural observers. The results show that financial records are kept manually and simply based on the values of honesty, trustworthiness, and mutual trust among members. This system creates social transparency even though it does not follow modern accounting standards. In addition, spiritual and cultural values are reflected through the slametan ritual as a form of gratitude and moral responsibility to God. This traditional accounting practice not only functions as a financial recording tool but also as a social mechanism that strengthens solidarity, maintains community integrity, and preserves local cultural values.